Pathogenetic and Clinical Aspects of Anti-Neutrophil Cytoplasmic Autoantibody-Associated Vasculitides - Lamprecht, Peter; Kerstein, Anja; Klapa, Sebastian; Schinke, Susanne; Karsten, Christian M.; Yu, Xinhua; Ehlers, Marc; Epplen, Jörg T.; Holl-Ulrich, Konstanze; Wiech, Thorsten; Kalies, Kathrin; Lange, Tanja; et al. (Frontiers in Immunology, 2018)
Anti-neutrophil cytoplasmic autoantibodies (ANCA) targeting proteinase 3 (PR3) and myeloperoxidase (MPO) expressed by innate immune cells (neutrophils, monocytes) are salient diagnostic and pathogenic features of small vessel vasculitis, comprising granulomatosis with polyangiitis, microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis and renal-limited vasculitis. Genetic studies suggest that ANCA-associated vasculitides (AAV) constitute separate diseases which share common immunological and pathological features, but are otherwise heterogeneous. The successful therapeutic use of anti-CD20 antibodies emphasizes the prominent role of ANCA and possibly other autoantibodies in the pathogenesis of AAV. However, in order to elucidate causal effects in AAV, a better understanding of the complex interplay eventually leading to the emergence of B lymphocytes that produce pathogenic ANCA remains a challenge. Different scenarios seem possible; among them the break of tolerance induced by a shift from non-pathogenic towards pathogenic autoantigen epitopes in inflamed tissue. This review gives a brief overview on current knowledge about genetic and epigenetic factors, barrier dysfunction and chronic non-resolving inflammation, necro-inflammatory auto-amplification of cellular death and inflammation, altered autoantigen presentation, alternative complement pathway activation, alterations within peripheral and inflamed tissue-residing T- and B-cell populations, ectopic lymphoid tissue neoformation, the characterization of PR3-specific T-cells, properties of ANCA, links between autoimmune disease and infection-triggered pathology and animal models in AAV.